Small Intestinal Bacterial Overgrowth Affects the Responsiveness to Colchicine in Familial Mediterranean Fever. (12th December 2017) - Verrecchia, E.; Sicignano, L. L.; La Regina, M.; Nucera, G.; Patisso, I.; Cerrito, L.; Montalto, M.; Gasbarrini, A.; Manna, R.
Abstract : Objective . Familial Mediterranean fever (FMF) is an autosomal recessive disease due to a MEFV gene mutation. Since Helicobacter pylori infection has been described to increase the severity and frequency of FMF attacks, we evaluate if overgrowth of small intestinal bacterial (SIBO), associated with a release of bacterial products, can affect the response to colchicine in FMF patients poorly responsive to colchicine. Methods . We revised our Periodic Fever Centre database to detect FMF patients who were poorly responsive to colchicine, without a well-defined cause of drug resistance. They were evaluated for SIBO presence, then treated with decontamination therapy. Results . Among 223 FMF patients, 49 subjects show colchicine resistance, and no other known causes of colchicine unresponsiveness has been found in 25 patients. All 25 patients underwent glucose breath test; 20 (80%) of them were positive, thus affected by SIBO. After a successful decontamination treatment, 11 patients (55%) did not show FMF attacks during the following three months (p < 0.01 ), while 9 of them revealed a significant reduction of the number of attacks compared to three months before (p < 0.01 ). Conclusion . The SIBO eradication improves laboratory and clinical features of FMF patients. Thus, patients with unresponsiveness to colchicine treatment should be investigated for SIBO.